Spatial analysis of advanced level health facilities in Jambi city in 2023 - Ramadhani, Suci; Noerjoedianto, Dwi; Amir, Andy (Institute of Computer Science (IOCS), 2024)
Background: The national health insurance system which implements a tiered referral system requires BPJS participants to visit the community health center as a First Level Health Facility (FKTP) before seeking treatment at an Advanced Level Health Facility (FKTl). Research Objective: To determine the availability and distribution of Jambi City Advanced Level (FKTL) facilities. Research method: Quantitative with an exploratory descriptive design. Research results: Show that all sub-districts in Jambi City have been reached by FKTL, Putri Ayu Community Health Center made the most referrals to FKTL at 5,927 due to being close to several FKTL, while the FKTL with the highest referrals was DKT Jambi Hospital, namely around 65,375. The most common illnesses referred to FKTL are hypertension, diabetes mellitus, coronary heart disease, stroke and kidney failure. Raden Mattaher Regional Hospital is a hospital that receives many referrals for this disease, one of the reasons is because it has the largest number of specialist doctors in Jambi City. Conclusion: The distribution of Jambi City Hospitals is quite even, the number of FKTL referrals can be influenced by the distance or distribution of health centers close to the FKTL and the availability or ability of medical personnel to treat referral diseases.